SILENT TEARS BEHIND RECYCLED OBNOXIOUS TRADITIONAL WIDOWHOOD PRACTICES IN NIGERIA: AN INTERPRETIVE PHENOMENOLOGICAL ANALYSIS - Tosin Emmanuel AKINDUYO (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
This study investigated the silent tears behind recycled obnoxious traditional widowhood practices in Nigeria. The age-long widowhood practices are embedded in trauma-laced traditional norms, negatively affecting the well-being of widows in Nigeria. This study adopted an Interpretative Phenomenological Analysis (IPA) qualitative design. Twenty-five (25) widows voluntarily participated in this study using snowball sampling techniques from different widows’ support groups. A semi-structured interview was used to obtain information from all participants. This enables widows to share their lived experiences of various traditional widowhood practices, which were regarded as obnoxious and dehumanizing to them. Data collection was conducted in seven (7) steps, using semi-structured interviews. It was concluded that recycled obnoxious traditional widowhood practices in Nigeria, as expressed by widows, are cruel treatments, financial constraints, loss of companions, disinheritance, sexual concerns, and assault/exploitation. It was recommended, among others, that, in line with Sustainable Development Goal 5, there should be a well-grounded legal framework that promotes gender equality, eradicates gender-based discrimination, and empowers all women.